FATTENING IN MALE BALI DUCKS WHICH WERE GIVEN INDIGOFERA (Indigofera zollingeriana) LEAF EXTRACT - M.S., Munir; Puger, A.W.; Mariani, N.P. (Jurnal Peternakan Tropika, 2024)
The research was conducted to study the effect of indigofera ( Indigofera zollingeriana ) leaf extract on fattening in eight-week-old male bali ducks. The experimental design used was a completely randomized design (CRD) with four treatments and five replications. Each replication consisted of six ducks, so the number of male bali ducks used was 120. The treatment applied was the provision of drinking water to male bali ducks with 0% indigofera ( Indigofera z ollingeriana ) leaf extract as a control (treatment A), while in treatment B, C, and D they were given indigofera ( Indigofera zollingeriana ) leaf extract through drinking water with a level of 2%, 4%, and 6% respectively. Rations and drinking water are given ad libitum. The variables observed were the percentage of pad fat, mesenteric fat, ventriculus fat, abdominal fat, and subcutaneous fat. The results showed that by giving indigofera ( Indigofera z ollingeriana ) leaf extract through drinking water significantly (P<0.05) increased the percentage of pad fat, mesenteric fat, ventricular fat, abdominal fat, and subcutaneous fat rather than control treatment. Based on the results of this study, it can be concluded that by giving indigofera ( Indigofera zollingeriana ) leaf extract with a level of 2% through drinking water can reduce the percentage of ventricular fat and subcutaneous fat, but with a level 4-6% it can increase the fat pad, mesenteric, ventriculus, abdominal, and subcutaneous of eight-week-old male bali ducks.